SISTEM INFORMASI AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS DALAM UPAYA MENINGKATKAN AKUNTABILITAS PUBLIK ORGANISASI NIRALABA (STUDI KASUS PONDOK PESANTREN AL MADINAH AL ISLAMI-PRABUMULIH) - Maryani Maryani; Kurniawan Kurniawan (Universitas Pendidikan Indonesia, 2022)
Integrated and accountable financial management is a form of accountability from the cottage to the foundation for the management and use of the resources that have been mandated. However, very few implementations are implemented in accordance with applicable accounting. The purpose of this study was to determine the extent to which the Classical Islamic Boarding School implemented an Accounting Information System (AIS) for cash receipts and disbursements in its transactions. This type of descriptive research with the method used is a qualitative approach and data collection used is a triangulation of sources and techniques. Data is collected through the following ways; interviews, observations, and documenting the data in the field, the further data collected was analyzed again using a case study method approach. This study states that the Al Madinah Al Islami Islamic Boarding School still has not implemented an actual accounting information system. Recording of transactions is carried out very simply, namely recording all cash receipts and disbursements, without going through the stages of the accounting system clearly, so that it cannot be described through a flowchart. accounting standards.